Attitudes of Indonesian Youth in Bandung towards English on Social Media - Dhea Mery Ad'hani; Isti Siti Saleha Gandana; Ernie D. A Imperiani (Universitas Pendidikan Indonesia (UPI), 2022)
The high use of social media platforms today and the status of English as an international language have driven many people across national borders to communicate using English. This study aims to explore the attitudes of a group of Indonesian youth in Bandung towards English in social media and to investigate the factors affecting their attitudes. The study adopts a qualitative approach and draws on Schiffman and Kanuk’s (2004) theory of attitude, which embraces the cognitive, affective, and conative dimensions. In addition, this study also uses Jendra’s (2010) theory on factors affecting language attitude. The results show that the majority of youth hold positive attitudes towards English in social media in each of the three aspects of attitude. The factors affecting their positive attitudes are the power and prestige of English and the social factor as the society at large has been accustomed to using English for global communication. This study implies the importance of English in the context of social media communication and raises people’s awareness of English for online international communication.